Duodenal biopsy findings in patients with renal amyloidosis - Başol CANBAKAN; Semahat KARAHİSAR and Selda SEÇKİN and Dilek OĞUZ and Erdal ESKİCİOĞLU and; yya ADANALI (Turkish Journal of Gastroenterology, 2019)
-